Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Sections 7.1-7.5 - Integrated Review - Radicals and Rational Exponents: 23

Answer

$3x\sqrt[3] (2x)$

Work Step by Step

$\sqrt[3] (54x^{4})=\sqrt[3] (27\times x^{3}\times2x)=\sqrt[3] 27\times \sqrt[3] (x^{3})\times\sqrt[3] (2x)=3x\sqrt[3] (2x)$ We know that $\sqrt[3] 27=3$, because $3^{3}=27$. We know that $\sqrt[3] (x^{3})=x$, because $(x)^{3}=x^{3}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.